A Phosphanthrene Oxide Host with Close Sphere Packing for Ultralow‐Voltage‐Driven Efficient Blue Thermally Activated Delayed Fluorescence Diodes. Issue 38 (21st August 2017) - Yang, He; Liang, Qianqian; Han, Chunmiao; Zhang, Jing; Xu, Hui
Abstract : A phosphanthrene oxide host, 5, 10‐diphenyl‐phosphanthrene 5, 10‐dioxide (DPDPO2 A ), with intra‐ and intermolecular hydrogen bonds achieves spheroidal cis ‐configuration and close sphere packing.DPDPO2 A realizes effective exciton suppression and excellent and balanced carrier transporting ability, both at the same time, demonstrating favorable photoluminescence quantum yield of 84% from its blue thermally activated delayed fluorescence (TADF) dye, namely bis[4‐(9, 9‐dimethyl‐9, 10‐dihydroacridine) phenyl]sulfone, doped films and high electron and hole mobility at the level of 10 −4 and 10 −5 cm 2 V −1 s −1, respectively.DPDPO2 A endows its blue TADF devices with record‐low driving voltages, e.g., turn‐on voltage of 2.5 V, and the state‐of‐the‐art efficiencies with maxima of 22.5% for external quantum efficiency and 52.9 lm W −1 for power efficiency, which is the best comprehensive performance to date of ultralow‐voltage‐driven blue TADF diodes. Abstract : A phosphanthrene oxide host, 5, 10‐diphenyl‐phosphanthrene 5, 10‐dioxide, with intra‐ and intermolecular hydrogen bonds achieves spheroidal cis ‐configuration and close‐sphere packing, resulting in effective exciton suppression and excellent and balanced carrier‐transporting ability, both at the same time, which endow its blue thermally activated delayed fluorescence (TADF) devices with a record‐low turn‐on voltage of 2.5 V and state‐of‐the‐art efficiencies.